Aging methods and age‐at‐death distributions: Does transition analysis call for a re‐examination of bioarchaeological data?. (30th December 2019) - Clark, Melissa A.; Simon, Allyson; Hubbe, Mark
Abstract: Age estimation of adult skeletal remains is notoriously difficult because the degenerative change of adult skeletons is far more variable across individuals, populations, and anatomical regions than the developmental changes that occur during growth. Additionally, age mimicry makes it difficult to discern between the true population age structure and the age structure produced as an artifact of the reference sample. Transition analysis is an age estimation method that was developed to improve the accuracy of age estimation, especially in older adults, by applying a stricter statistical framework based on multiple osteological age markers. Despite its availability since 2002, bioarchaeologists continue to rely heavily on traditional aging methods. However, since transition analysis has begun to gain popularity, it is necessary to identify how the choice of age estimation method affects interpretations about life in the past, especially when samples aged through transition analysis are compared to samples aged with traditional methods. This study evaluates the effect of aging methods on age‐at‐death distributions in a sample from the Late Archaic and Prehistoric periods in Northeast Ohio. Ninety‐three skeletons were aged using both traditional aging methods and transition analysis, and the results from both methods were compared. The two aging methods produced vastly different age‐at‐death distributions and significantly different survival curves. This study shows that bioarchaeologists should be wary of taking pre‐existing data at face value and should consider interpreting data using both traditional aging methods and transition analysis until the accuracy of transition analysis is more clearly established.